2020
DOI: 10.1002/art.41129
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cytotoxicity Profile of CD8+ T Cells in Ankylosing Spondylitis

Abstract: Objective Ankylosing spondylitis (AS) is an inflammatory arthritis in which men have a higher risk of developing progressive axial disease than women. Transcriptomic studies have shown reduced expression of cytotoxic cell genes in the blood of AS patients. HLA–B27 contributes the greatest risk for AS, suggesting a role for CD8+ T cells. This study was undertaken to profile AS patient cytotoxic cells with the hypothesis that an alteration in CD8+ T cells might explain the aberrant cytotoxic profile observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 21 publications
5
34
0
Order By: Relevance
“…Yet CD8 + T cells are signi cantly reduced in individuals with AS along with reduced expression of cytotoxic genes granzyme A (GZMA) and perforin (PRF1), but synovial uid levels of GZMA and GZMB were signi cantly elevated compared to the peripheral blood of the same patients. Intriguingly, the differences in cytotoxic gene expression were limited to men with AS [15,16]. In our study, while total CD8 + T cells were unchanged in axSpA, we identi ed a profound shift of cytotoxic cell populations in our study, and in particular, T cells expressing GZMB in the peripheral blood of individuals with CD-axSpA.…”
Section: Discussionsupporting
confidence: 46%
“…Yet CD8 + T cells are signi cantly reduced in individuals with AS along with reduced expression of cytotoxic genes granzyme A (GZMA) and perforin (PRF1), but synovial uid levels of GZMA and GZMB were signi cantly elevated compared to the peripheral blood of the same patients. Intriguingly, the differences in cytotoxic gene expression were limited to men with AS [15,16]. In our study, while total CD8 + T cells were unchanged in axSpA, we identi ed a profound shift of cytotoxic cell populations in our study, and in particular, T cells expressing GZMB in the peripheral blood of individuals with CD-axSpA.…”
Section: Discussionsupporting
confidence: 46%
“…Whether HLA-B27 could be mediating IEL activation in patients with SpA, and whether it is possible for these cells to home to the inflamed joints of these patients, is interesting to speculate. Relevant to this point, recent studies have revealed the presence of resident-like CD8 + T cells in axial spinal ligaments 134 , whereas other studies have demonstrated high frequencies of granzyme-producing CD8 + T cells with gut-related homing markers, in the peripheral joints of SpA patients 123,135 .…”
Section: Immunological Alterations In Spamentioning
confidence: 99%
“…Perforin and granzyme B also exist extracellularly in blood serum and plasma. There are only limited reports about the serum concentrations of perforin associated with pathophysiological status 18‐24 . In our study, perforin, but not granzyme B, was measured by ELISA.…”
Section: Discussionmentioning
confidence: 77%